From emissions to emotions: Exploring the impact of climate change on happiness across 140 countries - Jeremy Ko; Chun Kai Leung; Xiaoxian Chen; David A. Palmer (Global Transitions)
This study examines the relationship between climate change and happiness using panel data from 140 countries between 2008 and 2020. We investigate whether greenhouse gas (GHG) emissions—specifically carbon dioxide (CO₂), methane (CH₄), and nitrous oxide (N₂O)—influence subjective well-being, while controlling for socio-economic factors such as GDP per capita, child mortality, and inequality. The analysis reveals that while emissions have limited direct effects on happiness, economic development and public health remain critical drivers of well-being. Notably, developed countries show a negative association between emissions and happiness, highlighting growing environmental concerns, whereas economic growth plays a dominant role in shaping happiness in developing countries. Robustness checks, including two-stage least squares (2SLS) regression and panel-corrected standard errors (PCSE), confirm the stability of the findings. These results suggest that climate policies should align with economic and social priorities to enhance well-being. We recommend adopting context-specific strategies—such as sustainable development and adaptation measures—that account for regional differences in environmental impacts. This study contributes to the growing literature on the climate-happiness nexus and provides valuable insights for policymakers striving to balance climate action with societal well-being.